1997
DOI: 10.1590/s0100-879x1997001100002
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the pathophysiology of lipoprotein(a) in the athero-thrombotic process

Abstract: Lipoprotein Lp(a) is a major and independent genetic risk factor for atherosclerosis and cardiovascular disease. The essential difference between Lp(a) and low density lipoproteins (LDL) is apolipoprotein apo(a), a glycoprotein structurally similar to plasminogen, the precursor of plasmin, the fibrinolytic enzyme. This structural homology endows Lp(a) with the capacity to bind to fibrin and to membrane proteins of endothelial cells and monocytes, and thereby to inhibit plasminogen binding and plasmin generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…1), and by binding of LAP to mannose-6-phosphate receptors (17,19 and references therein). Lipoprotein Lp(a) inhibits activation of plasminogen to plasmin and thereby negatively affects activation of TGF-␤ (reviewed in ref 22 and references therein). Other mechanisms that have been implicated in activation of latent TGF-␤ are deglycosylation of LAP (23), exposure to reactive oxygen species (24), or acidic cellular microenvironments (25).…”
Section: Control Of Tgf-␤ Bioactivitymentioning
confidence: 99%
“…1), and by binding of LAP to mannose-6-phosphate receptors (17,19 and references therein). Lipoprotein Lp(a) inhibits activation of plasminogen to plasmin and thereby negatively affects activation of TGF-␤ (reviewed in ref 22 and references therein). Other mechanisms that have been implicated in activation of latent TGF-␤ are deglycosylation of LAP (23), exposure to reactive oxygen species (24), or acidic cellular microenvironments (25).…”
Section: Control Of Tgf-␤ Bioactivitymentioning
confidence: 99%
“…This allows Lp(a) to bind to fibrin and to the membrane proteins of endothelial cells and monocytes. Since Lp(a) resembles both LDL and plasminogen, it could possibly act as a link between atherosclerosis and thrombosis [41]. The accumulation of Lp(a) on the surface of fibrin and cell membranes as well as the inhibition of plasmin generation favors the deposition of fibrin and cholesterol at sites of vascular injury.…”
Section: Pathophysiology Of Lp(a)mentioning
confidence: 99%
“…Short apo(a) alleles increased Lp(a) levels, thus favoring atherosclerosis. Also, since the inverse relationship between apo(a) size & Lp(a) is not linear, this suggests a functional diversity among the Hepatic secretion lower for large apo(a) isoforms & since most individuals are heterozygous for two different isoforms, so typically the smallest isoform dominates in plasma apo(a) isoforms [41]. Another study by Hervio et al [59] suggested that the variable number of kringles in apo(a) influences its ability to bind to fibrin.…”
Section: Genetic Polymorphism and Functional Heterogeneity Of Lp(a)mentioning
confidence: 99%
“…In letzter Zeit wurde auch versucht, andere Krankheiten im Kaninchenmodell zu studieren und Proteine in vivo in Milch bzw. Blut zu 16.2 Transgene Kaninchen 173 exprimieren (Angles-Cano 1997, Taylor 1997. Kaninchen haben zudem eine große Bedeutung für die Generierung von Antiseren, und sind das einzige kleinere Tier, das mit dem humanen Immundefizienz Virus (HIV) infizierbar ist.…”
Section: Transgene Kaninchenunclassified